The Challenges of Implementing the Merdeka Curriculum in Arabic Language Learning: Perspectives from Indonesian Lecturers and Students - Rohimah, Umniatur; Sholikha, Imiatus; Isnainiyah (Institut Agama Islam Negeri Palangka Raya, 2023)
This research aims to identify and explain the issues or challenges faced by the Sunan Kalijogo Islamic Institute in Malang, especially the Arabic Language Education program, in implementing the Merdeka Curriculum. The focus of this research includes the learning process using the Merdeka curriculum, inhibiting factors, and solutions to overcome challenges in implementing the Merdeka curriculum in Arabic language learning. Data collection is conducted through observation, interviews, and documentation. This research is a qualitative, descriptive study, where the method used involves describing and analyzing a phenomenon by describing a number of variables related to the issues and the unit under study. The next step is to analyze qualitative data from the research results related to the challenges of Arabic language learning. Based on the research findings, it is concluded that the challenges of implementing the Merdeka curriculum in Arabic language learning at the Sunan Kalijogo Islamic Institute in Malang are divided into three aspects: institutional, student-related, and lecturer-related. The researcher also found several solutions and alternatives that can help overcome and address the challenges of implementing the Merdeka curriculum in Arabic language learning.